Interfiber bonding and fiber segment activation in paper - Hannu Paulapuro; Anna K. Vainio (BioResources, 2007)
Bonding and activation in paper were studied with the help of laboratory test sheets and common paper strength tests. Different papermaking furnishes and raw material treatments were used to examine the effects they have on bonding and activation. Furthermore, various boundary conditions during drying were included to single out the influence of bonding and activation on paper properties. It was found that bonding is clearly increased by beating of kraft pulp, starch addition, and thermomechanical pulp fines, whereas activation benefited most from beating and addition of reinforcement fibers to mechanical pulp based furnishes. Subjecting test sheets to increasing amounts of drying stress affected activation positively, and bonding negatively. The increase in activation did not seem to be dependent on the beating degree of chemical pulp fibers. Bonding, on the other hand, deteriorated more significantly in sheets made of extensively beaten kraft fibers, i.e. in sheets where the initial bonding potential was higher. Commonly used paper strength measurements provide dependable and accurate tools for assessing the effect of different variables on both bonding and activation. A short literature survey of bonding and activation is also provided.